2015
DOI: 10.5812/asjsm.22643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on the Quality of Life and Echocardiography Parameter of Systolic Function in Patients with Chronic Heart Failure: a Randomized Trial

Abstract: Background:Ejection fraction promotion in heart failure patients reduces mortalities and limitations.Objectives:This study was to investigate the effect of exercise on ejection fraction of chronic heart failure patients.Patients and Methods:The present study was conducted on patients with chronic heart failure. 66 patients were divided randomly into two experimental and control groups of 33 each. The subjects were male and female. The patients in experimental group followed an exercise program three sessions p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Physical activity generally improves QoL, aerobic fitness, and cardiac function in HF patients (Beniaminovitz et al, 2002 ; Harris et al, 2003 ; Gary et al, 2004 ; Koukouvou et al, 2004 ; Davidson et al, 2010 ; Hassanpour Dehkordi and Khaledi Far, 2015 ). However, this is not always the case, as Keteyian et al ( 1999 ) showed no significant change in QoL after 6 months' aerobic training in male HF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity generally improves QoL, aerobic fitness, and cardiac function in HF patients (Beniaminovitz et al, 2002 ; Harris et al, 2003 ; Gary et al, 2004 ; Koukouvou et al, 2004 ; Davidson et al, 2010 ; Hassanpour Dehkordi and Khaledi Far, 2015 ). However, this is not always the case, as Keteyian et al ( 1999 ) showed no significant change in QoL after 6 months' aerobic training in male HF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Both measurements from pre- to post-test were statistically significant improvements for the yoga participants. Recently, a randomized trial by Hassanpour Dehkordi and Khaledi Far [ 56 ] utilized echocardiography to measure left ventricular diameter and ejection fraction in HF patients before and after 24 weeks of aerobic exercise training. They reported a significant improvement in left ventricular diameter and ejection fraction in the experimental group in comparison to the control group at the end of the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…[ 6 ] An exercise program, developed based on the physical conditions of patients, can promote the quality of life in patients with chronic disease. [ 10 11 12 13 14 ]…”
Section: Introductionmentioning
confidence: 99%